2014
DOI: 10.5194/hess-18-479-2014
|View full text |Cite
|
Sign up to set email alerts
|

Modelling pesticide leaching under climate change: parameter vs. climate input uncertainty

Abstract: Abstract. Assessing climate change impacts on pesticide leaching requires careful consideration of different sources of uncertainty. We investigated the uncertainty related to climate scenario input and its importance relative to parameter uncertainty of the pesticide leaching model. The pesticide fate model MACRO was calibrated against a comprehensive one-year field data set for a well-structured clay soil in southwestern Sweden. We obtained an ensemble of 56 acceptable parameter sets that represented the par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 60 publications
0
5
0
2
Order By: Relevance
“…Using multiple climate models with different greenhouse gas emission scenarios allows the integration of more variability (Fernández et al, 2017). The climate change component of the model could have been improved by using more recent and alternative climate models, as recommended by, for example, Steffens et al (2014) and Moe et al (2022). These authors mentioned that using an ensemble of various global and regional climate models and various greenhouse gas emission scenarios would potentially enable more robust predictions of environmental impacts such as chemical exposure in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiple climate models with different greenhouse gas emission scenarios allows the integration of more variability (Fernández et al, 2017). The climate change component of the model could have been improved by using more recent and alternative climate models, as recommended by, for example, Steffens et al (2014) and Moe et al (2022). These authors mentioned that using an ensemble of various global and regional climate models and various greenhouse gas emission scenarios would potentially enable more robust predictions of environmental impacts such as chemical exposure in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple climate models with different greenhouse gas emission scenarios allows integration of more variability (Fernández et al, 2017). The model could he been improvement by using more and different climate models as some papers by Steffens et al (2014) and Moe et al (2022) recommended. These mentioned that using an ensemble of various lobal and regional climate models together with various greenhouse gas emission scenarios would potentially enable more robust estimations of pesticide losses in future.…”
Section: Discussionmentioning
confidence: 99%
“…Printer-friendly version Discussion paper for projecting some important hydrological variables. Another study also demonstrated that model parameters could be of major importance for projecting changes in waterquality (Steffens et al, 2014).…”
Section: Interactive Commentmentioning
confidence: 96%